Comparison of structural and spectroscopic properties of Ho3+-doped niobate compounds - Guene-Girard, S.; Courtois, J.; Dussauze, M.; Heintz, J-M.; Fargues, A.; Roger, J.; Nalin, M. [UNESP]; Cardinal, T.; Jubera, V. (Elsevier, 2021)
Ho3+-doped YNbO4 and Y3NbO7 phosphors were synthesised via a co-precipitation synthesis route. Structural characterisation and spectroscopic properties were performed as a function of the Ho3+ concentration. The Rietveld type-refinement confirms the stabilisation of the pure monoclinic Fergusonite YNbO4 phase at the highest temperatures, but the quadratic phase is stabilised for the lowest temperature, whereas a pure cubic fluorite Y3NbO7 phase was observed for all of the heat treatments. Raman and infrared spectroscopies were used to compare the cation-oxygen vibrational modes. Emission spectra and up-conversion processes were obtained under excitation at 445 and 975 nm respectively. For a similar Ho3+ content, the energy transfers observed show differences between the two crystalline compounds that are related to a stronger interaction between the holmium cations in the fluorite host lattice.
Keywords: Energy transfer; Luminescence; Niobate; Raman; Rare earth